In vitro effects of aqueous leaf extracts of moringa oleifera on human sperm - Moichela, Faith Tebatso (My University, 2021)
Infertility affects nearly 186 million couples globally, with male factors contributing to half of the cases. Oxidative stress is an established cause of declining semen quality. Moringa oleifera has proven antioxidants. This study aimed to investigate in vitro effects of aqueous leaf extract of M. oleifera on human sperm functions. Semen samples from donors (n = 40) and patients (n = 30) were washed with HTF-bovine serum albumin (BSA), and then incubated with various concentrations of M. oleifera (0, 0.625, 6.25, 62.5, and 625 μg/ml) at 37°C for 1 hour. Sperm motility, vitality, mitochondrial membrane potential (MMP), reactive oxygen species (ROS), DNA fragmentation, capacitation, and acrosome reaction were assessed. Sperm motility, vitality, MMP, and capacitation were enhanced, while ROS production, and DNA fragmentation decreased after M. oleifera treatment. Uncapacitated spermatozoa increased significantly with a reduction in acrosome reaction in donors. M. oleifera antioxidant compounds suppressed excessive ROS, preserved mitochondrial membrane, DNA and acrosome integrity, while enhancing sperm motility and viability.
Thesis (M.Sc. (Medical Sciences)) -- University of Limpopo, 2020
Keywords: Sperm function; Oxidative stress; Infertility; Antioxidants; Moringa oleifera; Moringa oleifera; Infertility, Male.; Reproductive system, Male; Spermatozoa; Oxidative stress; Antioxidants